2008
DOI: 10.1007/s00425-008-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of mitochondrial phosphate transporter in accelerating bud dormancy release during chilling treatment of tree peony (Paeonia suffruticosa)

Abstract: A cDNA clone was isolated from tree peony (Paeonia suffruticosa) subtractive cDNA library of burst buds and characterized with regard to its sequence, expression in response to chilling treatment during the release of bud dormancy, and its function in transgenic Arabidopsis thaliana. The clone, designated as PsMPT, contains 1,615 nucleotides with an open reading frame of 1,119 nucleotides, and the deduced amino acid sequence shows high homology with mitochondrial phosphate transporters (MPTs) from various orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Comparing with other fruit plants, the knowledge about dormancy release in tree peony is relatively limited. Huang et al reported 31 unique genes that might be associated with dormancy release during chilling treatments in a subtractive cDNA library, but most of them were related to structural function (Huang et al, 2008a(Huang et al, , 2008b. Currently only 2204 pieces of EST are found in National Center for Biotechnology Information (NCBI) database, and most of them were recently submitted with a purpose for bud differentiation in tree peony (Shu et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Comparing with other fruit plants, the knowledge about dormancy release in tree peony is relatively limited. Huang et al reported 31 unique genes that might be associated with dormancy release during chilling treatments in a subtractive cDNA library, but most of them were related to structural function (Huang et al, 2008a(Huang et al, , 2008b. Currently only 2204 pieces of EST are found in National Center for Biotechnology Information (NCBI) database, and most of them were recently submitted with a purpose for bud differentiation in tree peony (Shu et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…c Northern blotting analysis of tree peony PsMYB1 expression after 0, 7, 14, 21 and 28 days chilling treatment. d Expression analysis of PsMYB1 in the tree peony flower buds enduring 7 and 21 days chilling treatments and then transferred to the greenhouse using qPCR Plant Growth Regul and Gai et al screened different stages during endo-dormancy release (Huang et al 2008b;Gai et al 2013). Based on morphological changes and global mRNA profiling of differentially expressed genes, they found that flower buds that received less than 18 days chilling treatment were regarded as endo-dormancy in physiological status, while those that received more than 18 days of chilling treatment were regarded as eco-dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…In petunia corollas, a high-affinity phosphate transporter gene PhPT1 (PhPht1;1), which shows to be up-regulated during senescence and possibly to be functional in Pi translocation during senescence, shows a rapid increase followed with low levels of ethylene treatment (0.1 mM) (Chapin and Jones, 2009). The mRNA accumulation of PsMPT in tree peony was strongly induced by chilling treatment during the release of bud dormancy (Huang et al, 2008). Together, these results imply that the plant Pi transporter genes have a complicated transcriptional mechanism regulated by many environmental factors, which include Pi, Zn and other unknown inorganic nutrients, and other factors.…”
Section: Expression Pattern In Response To Environmental Factorsmentioning
confidence: 94%
“…Mpt1 contains an open reading frame of 1092 bases encoding a 364 amino acid polypeptide, much fewer than those in cytosol membrane and plastid envelope (Kiiskinen et al, 1997). Other mitochondrial phosphate transporter genes have also been identified in soybean, maize, rice, and Arabidopsis (Takabatake et al, 1999), Lotus japonicus (Nakamori et al, 2002), and tree peony (Paeonia suffruticosa) (Huang et al, 2008). It is currently known that most of the mitochondrial phosphate transporters in plants have generally about six of the conserved transmembrane domains, and nearly half of those targeted in cytosol membrane and plastid envelope.…”
Section: Cellular Location Of the Plant Pi Transportersmentioning
confidence: 96%
See 1 more Smart Citation